Peran Etika Akademik terhadap Pembentukan Karakter dan Kualitas Pendidikan Mahasiswa di Perguruan Tinggi - Muhammad Alif; Dea Emilya Kabrina; Syahrani Seren Harahap; Rizky Fadilah Raihanah; Muhammad Shiddiq Harahap; Parulian Sibuea (Arden Jaya Publisher, 2026)
Abstract This study aims to determine the role of academic ethics in shaping student character and improving the quality of education in higher education institutions. Academic ethics are important guidelines in creating honest, disciplined, responsible, and professional academic behavior within the higher education environment. The development of digital technology and the use of Artificial Intelligence (AI) in education have also created various new challenges, such as plagiarism, task manipulation, and misuse of technology in the learning process. Therefore, the implementation of academic ethics is very important in shaping student character and maintaining the quality of education. This study uses a qualitative research method with a library research approach. Data were obtained from various scientific journals, articles, and reliable references related to academic ethics, student character building, and the quality of education in higher education institutions. The data were analyzed descriptively to gain an understanding of the relationship between academic ethics, character building, and the quality of student education. The results of the study indicate that academic ethics have a significant influence on the formation of student character, such as honesty, discipline, responsibility, integrity, and professionalism. In addition, the implementation of academic ethics is also able to create a healthy learning culture and improve the quality of student education. On the other hand, low awareness of academic ethics can lead to various academic violations such as plagiarism, cheating, task manipulation, and misuse of digital technology and AI. Therefore, higher education institutions need to strengthen the implementation of academic ethics so that students are able to use technology wisely and become qualified graduates with integrity. Key Words: Academic ethics, character building, quality of education, education.